Estadisticas de produccion en Brazil - Luna, EA (International Center for Tropical Agriculture, 1973)
Statistical data are given on cassava, rice, common beans, corn, cotton and sugar cane production in Brazil from 1969-70. A total of 2,029,373 ha were planted to cassava, yielding 30,073,943 tons. Data are broken down for 8 states. (CIAT)